QUALITATIVE AND QUANTITATIVE EVALUATION OF BIOACTIVE PHYTOCHEMICALS IN LEAF POWDER OF WIDELY GROWN PURSLANE (PORTULACA OLERACEA) - Odo, Chrysanthus Chukwuemeka; Ugo, Henry Chinecherem; Ibekwe, Maureen Ifeyinwa; Odo, Adlyne Chinagorom (FUDMA JOURNAL OF SCIENCES, 2025)
Some of our locally available underutilized crops are rich in phytochemicals with numerous untapped health benefits. The study evaluated the qualitative and quantitative bioactive phytochemicals in leaf powder of widely grown purslane (Portulaca oleracea). Fresh leaves of Portulaca oleracea collected from International Academy of Ethnomedicine, Igbuzo, Delta State, Nigeria were sorted, surfaces sterilized after washing them thoroughly in tap water to remove adhering dust and particles. The fresh cleaned leaves were dried under shade at room temperature, grinded into powder, and packaged. This was followed by the determination of its qualitative and quantitative bioactive phytochemical properties using standard analytical process. Data generated were statistically analyzed using the SPSS version 23.0 and results presented as means and standard deviations. The results indicated that the vegetable had more abundant (qualitative property) of alkaloid, flavonoid, terpenoids, total phenolics and reducing sugars, respectively; and less abundant of steroids, tannins, and glycosides while saponin was not detectable. Quantitatively, it contained 359 ± 16.10mg total phenolics, 131.11 ± 8.50mg alkaloid, 80.7 ± 3.29mg reducing sugar and no quantity of saponin was detected. The study showed that widely grown purslane (Portulaca oleracea) leaf powder was qualitatively and quantitatively rich in bioactive phytochemicals. We need to join hands in harnessing the potentials embedded in this underutilized vegetable by creating massive awareness on the benefits in not only helping to mitigate the cause of many diet-related non-communicable chronic diseases but also in the prevention and management of some chronic and degenerative diseases.